Chaperone‐mediated autophagy receptor modulates tumor growth and chemoresistance in non–small cell lung cancer. Issue 11 (7th September 2020) - Ichikawa, Akihiro; Fujita, Yu; Hosaka, Yusuke; Kadota, Tsukasa; Ito, Akihiko; Yagishita, Shigehiro; Watanabe, Naoaki; Fujimoto, Shota; Kawamoto, Hironori; Saito, Nayuta; Yoshida, Masahiro; Hashimoto, Mitsuo; et al.
Abstract: Chaperone‐mediated autophagy (CMA) is a lysosomal degradation pathway of selective soluble proteins. Lysosome‐associated membrane protein type 2a (LAMP2A) is the key receptor protein of CMA; downregulation of LAMP2A leads to CMA blockade. Although CMA activation has been involved in cancer growth, CMA status and functions in non–small cell lung cancer (NSCLC) by focusing on the roles in regulating chemosensitivity remain to be clarified. In this study, we found that LAMP2A expression is elevated in NSCLC cell lines and patient's tumors, conferring poor survival and platinum resistance in NSCLC patients. LAMP2A knockdown in NSCLC cells suppressed cell proliferation and colony formation and increased the sensitivity to chemotherapeutic drugs in vitro. Furthermore, we found that intrinsic apoptosis signaling is the mechanism of cell death involved with CMA blockade. Remarkably, LAMP2A knockdown repressed tumorigenicity and sensitized the tumors to cisplatin treatment in NSCLC‐bearing mice. Our discoveries suggest that LAMP2A is involved in the regulation of cancer malignant phenotypes and represents a promising new target against chemoresistant NSCLC. Abstract : Lysosome‐associated membrane protein type 2a (LAMP2A) is the key receptor protein of chaperone‐mediated autophagy (CMA). Downregulation of LAMP2A leads to CMA blockade. Our discoveries suggest that LAMP2A is involved in the regulation of cancer malignant phenotypes through CMA modulation and represents a promising new target against chemoresistant non–small cell lung cancer (NSCLC).